PANEL PARTISI RUANGAN PORTABLE DENGAN SISTEM ENGSEL DETACHABLE - Hidayat, Rafi; Muladi, Edy (Anggada : Jurnal Desain dan Seni, 2021)
Partition is one of the elements that divides the room into several parts. Many also refer to partitions as "dividers" or "screens". In places such as multipurpose rooms, museums, exhibition halls and events, which usually contain temporarily scheduled events in the room, partitions are often used for various needs either as room dividers, booths or as walls for art works such as paintings. From these activities, selecting the appropriate partition type is very important to support the ease of installation or function of the partition itself. The author tries to explore the design of the partition panel with the incorporation of a hinge system to produce movement and connections that have many uses so that the application of the partition panels can support all the needs of the room and the events held. Apart from the usability point of view, the author also explores the material aspects that will be designed on the panel so that it is lighter than most partitions. With a light weight it will also facilitate the process of dismantling the partition panels.